Estudo e aplicações da interface grafeno-água - Leonel Muniz Meireles (2020)
Graphene is a two-dimensional (2D) material composed only of carbon atoms, which has been widely studied due to its electrical, mechanical and optical properties. The combination of this material with some characterization techniques has achieved important achievements, especially in the development of biosensors. However, the use of graphene for such purposes begins with the challenge of understanding all the properties of this material in the presence of liquid media. Thus, the first proposal of this thesis is to improve the understanding of the electrical properties of graphene, when it becomes at the air/water interface. We conducted this study by building a device that allowed us to study the interaction of graphene suspended over water, that is, without the presence of substrates. We observed that the abrupt decrease in the resistivity of suspended graphene in the presence of water is electromechanical in nature, with a load transfer effect of much less magnitude, if any, than mechanical effects. This result not only clears up some basic scientific enigmas (transferring charge from water to graphene), but it also unlocks new applications for small fluid hybrid systems. In a second approach, we manufacture a micro-hole platform for analyzing biomaterials in liquid environments with nanoscale infrared spectroscopy. In this second work, using the graphene / liquid interface, together with the SINS technique (Synchrotron Infrared Nano-spectroscopy), we obtain the infrared “fingerprint” of fluids, biological and chemical, such as Dimethyl Sulfoxide (DMSO), Potassium dihydrogen phosphate (KH2PO4) and pyrenobutanoic acid succinimidyl ester (PBSE). In addition, we demonstrate the nanospectroscopy of fragments of human serum albumin (HSA) in water with a clear view of the spectral signatures of proteins and their secondary structures through the vibrational response of the amide bands I-II.